Views of Turkish veterinary practitioners on the veterinary consultation - Ozkul, T.; Genc, S. V.; Dogan, O.; Ozen, A. (British Veterinary Assoc, 2008)
[Abstract Not Available]
Keywords: Expectations; Skills